Ethephon Reduces Lodging and Enhances Seed Yield and Quality in Onion - Yalamalle, V. R.; Arunachalam, T.; Kumari, R.; Ithape, D. M.; Ghosh, S.; Singh, M. (International Journal of Bio-resource and Stress Management, 2021)
Onion is an important vegetable crop grown in almost all parts of the World as a flavouring agent in food preparation. It is propagated by seeds and the seed crop is affected by several fungal, viral and bacterial diseases which cause lodging and reduces the seed yield and quality. Onion seed crop was sprayed with different concentration of ethephon (0, 100, 200, 400, 600, 800 and 1000 ppm) for two duration at 45 or 45+60 days after planting during (DAP) during 2018-19 and 2019-20 rabi seasons. The effect of ethephon on seed yield and seed quality was studied. In comparison to control ethephon application significantly reduced scape length and % lodging by 38.73% and 42.52% respectively. There was 31.90% and 89% enhancement in scape diameter and yield respectively. Ethephon spray also enhanced seed quality, highest germination and seed vigour was recorded in plants sprayed with 600 ppm ethephon at 45 and 60 DAP which was 19% and 51.65% higher than control. Highest seedling dry weight was observed in plants sprayed with 100 ppm ethephon at 45 DAP. Among the treatments, 100 and 200 ppm ethephon applied at 45 DAP had lower lodging and higher seed yield and seed quality. Hence spraying of onion seed crop with 100 ppm ethephon at 45 DAP is beneficial for getting higher seed yield and quality.